Exploring the role of uterine fibroids in promotion of cardiovascular diseases by diabetes exposure: Findings from national health and nutrition examination survey 1999–2006 - Li, Bin; Yuan, Zhen; Zhang, Yizhi; Li, Feng; Huang, Lin; Yang, Zhihui; Liu, Haiyue; Liu, Zuheng (Frontiers in Cardiovascular Medicine, 2022)
Objectives: The relationship between uterine fibroids (UF) and cardiovascular diseases (CVDs) in diabetes population seemed remain undetermined in previous studies. The aim of this study was to explore the association of uterine fibroids and cardiovascular diseases by using the database from NHANES. To further evaluate the connection between UF and CVDs we also tested the potential differences due to diabetes exposure. Methods: NHANES data (1999-2006) were collected and used in this study. A total of 5509 individuals were included and analyzed. Student t test and chi-squared test were used to explore the demographic characteristic between uterine fibroids and non-uterine fibroids groups. Logistic regression analysis was performed to determine the odds ratios of uterine fibroids and covariates. Results: Female participants were divided into uterine fibroids (n = 694, 12.60%) and non-uterine fibroids (N = 4815, 87.40%) groups. The incidence of cardiovascular diseases in uterine fibroids patients (n = 245, 35.30%) were higher than non-uterine fibroids individuals (n = 776, 16.12%) (p < 0.001). In addition, each subtype of CVDs were also different, which contains hypertension (33.29% vs 15.31%, p < 0.001), hearth failure (1.59% vs 0.52%, p < 0.01), angina (2.59% vs 0.62%, p < 0.001), heart attack (1.73% vs 0.58%, p< 0.01) and coronary heart disease (1.44% vs 0.54%, p < 0.01). The odds ratios of CVDs according to logistic regression were 2.840 (95% CI: 2.387-3.379) for uterine fibroids patients (p < 0.001), while the odds ratios were 1.438 (95% CI: 1.175-1.760) after taking account for the age, BMI, diabetes, race, education and annual family income (p < 0.001). In addition, secondary analysis indicated more adverse effects in by UF exposure on CVDs risk among non-diabetes individuals (OR = 1.389, 95%CI = 1.124-1.718, p < 0.01) than diabetes patients (p = 0.063). Conclusions: Overall, uterine fibroids were positively associated with CVDs, and this effect seem blunted by diabetes exposure.